2007
DOI: 10.1103/physrevb.76.041102
|View full text |Cite
|
Sign up to set email alerts
|

Near-field interactions between a subwavelength tip and a small-volume photonic-crystal nanocavity

Abstract: The fundamentals of the near-field interaction between a subwavelength metallic tip and a photonic-crystal nanocavity are investigated experimentally and theoretically. It is shown experimentally that the cavity resonance is tuned without any degradation by the presence of the tip and that the reported near-field interaction is strongly related to the field distribution within the nanostructure. Then, in light of a perturbation theory, we show that this interaction is selectively related to the electric field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
68
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 16 publications
5
68
1
Order By: Relevance
“…The reconstructed field patterns are an approximation of the Bloch modes propagating in the system and moreover, they are not necessarily orthogonal because of quasi-interference. Although the effect of the tip is far from straightforward ( [5,20,21]), we anticipate that the comparison between calculated modes of an optical system and reconstructed modes could lead to methods to deduce the response function of a near-field tip. Next, we demonstrate the power of the reconstruction algorithm by studying the transverse behavior of TE-like mode (A) versus wavevector.…”
Section: Samples and Methodsmentioning
confidence: 99%
“…The reconstructed field patterns are an approximation of the Bloch modes propagating in the system and moreover, they are not necessarily orthogonal because of quasi-interference. Although the effect of the tip is far from straightforward ( [5,20,21]), we anticipate that the comparison between calculated modes of an optical system and reconstructed modes could lead to methods to deduce the response function of a near-field tip. Next, we demonstrate the power of the reconstruction algorithm by studying the transverse behavior of TE-like mode (A) versus wavevector.…”
Section: Samples and Methodsmentioning
confidence: 99%
“…However, only low-Q cavities have been studied so far and the very first attempts at probing small volume cavities have shown that the near-field probes ͓SNOM probes in Ref. 12 and atomic force microscopy ͑AFM͒ probes in Refs. 13 and 14͔ strongly alter-or even completely disrupt in the case of AFM probes-the light confinement mechanism inside the cavity.…”
mentioning
confidence: 99%
“…12 12,13,15 and the classical SNOM collection-scanning mode. [8][9][10][11] The differences between these two imaging methods are discussed in light of the recorded images by comparing them with three-dimensional ͑3D͒ calculations of the cavity mode.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is because, whereas the mode volume of state-of-the-art macroscopic cavities is on the order of 10 5 μm 3 , a photonic crystal nanocavity typically has a mode volume of a cubic wavelength. Because of this small mode volume, a photonic crystal nanocavity can easily be tuned by bringing a nano-object into the near field of the cavity [10][11][12]. For experiments in cavity quantum electrodynamics [13][14][15], a single emitter needs to be brought into the near field of the cavity.…”
mentioning
confidence: 99%